All optical timing extraction with frequency division using a twin section laser diode. - HEGARTY, JOHN (My University, 1993)
All-optical timing extraction from a coded line signal with division of the extracted clock frequency is demonstrated using a single twin-section self-pulsating laser diode. Either the bit-rate clock or a submultiple of the bit-rate clock can be extracted, depending only on the dc biases applied to the self-pulsating laser diode. Timing extraction is carried out for the first time without optical injection locking of the self-pulsating laser diode by the optical data source.
PUBLISHED
Keywords: Physics